ESTIMATION OF MORTALITY RATES OF THE OIL SARDINE, SARDINELLA LONGICEPS VAL. - Annigeri, G G (Indian Journal of Fisheries, 2011)
The mortality rates of oil sardine, Sardinella longiceps from Karwar have been estimated based on the age composition of the fishery by adopting the method of Beverton and Holt. The values obtained are 2.43, 1.57, 3.70 and 2.96 for instantaneous total mortality and 0.98, 0.12, 2.25 and 1.51 for the fishing mortality durig 1965-66,1966-67, 1967-68 and 1968-69 seasons respectively. The natural mortality obtained in the final iteration process is 1.45. The estimation shows considerable changes from year to year ’ inthe values of both total and fishing mortalities due to short-term changes in abundance offish.